Communication, cooperation & conflict in quorum sensing bacteria - Popat, Roman (2012)
The scientific community has gathered an extremely detailed and sophisticated understanding of the genetic and molecular underpinnings of microbial communication. How these microbial communication systems arise and are maintained over evolutionary time-scales however has received relatively little attention. Some major questions remain unanswered such as; what is the function of small diffusible molecules? How does population structure affect the dynamics of social communication and what is the link between the ecology of communication and the virulence of a pathogenic population? Borrowing concepts from evolutionary theory can help to unravel these fundamental questions in the context of microbial communication as it has done in other taxa displaying social behaviours. In addition microbial model organisms in which molecular and genetic tools are abundant lend enormous power to empirical tests of evolutionary theory. This work combines both of these in an attempt to understand the evolution of bacterial communication using the model organism Pseudomonas aeruginosa and its well characterised Quorum Sensing systems. Specifically the focus is in three areas. Firstly this study reveals that the stability of bacterial signalling is vulnerable to perturbations in cost and benefit and genetic conflict. Secondly this study finds that spatial structure (biofilm vs planktonic) influences the outcome of social competition over signalling and reduces population viability. Thirdly this study finds that interspecific and intraspecific competition over public goods impose divergent selective pressures on communication.